PENGARUH KEBIJAKAN DIVIDEN DAN LEVERAGE KEUANGAN TERHADAP VOLATILITAS HARGA SAHAM DENGAN CEO PEREMPUAN SEBAGAI PEMODERASI - Sinta Jeneca, Ni Putu; Diantini, Ni Nyoman Ayu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.10.TAHUN.2024DO - 10.24843/EEB.2024.v13.i10.p06, 2024)
This study aims to determine the effect of dividend policy and financial leverage on stock price volatility moderated by female CEO s using an associative quantitative approach. Using data registered as non-financial companies on the Kompas100 Index during the period 2018 to 2022. Data is accumulated and classified using the purposive sampling method or sample determination according to predetermined criteria so that the number of observation data obtained is 105 data from 32 non-financial companies which will be processed using SPSS 25.0 software using the Moderated Regression Analysis (MRA) technique. The test analysis will be carried out with descriptive statistical analysis and inferential analysis which then proves that dividend policy has a negative impact on stock price volatility, financial leverage has a positive correlation with stock price volatility, while female CEO s are unable to correlate dividend policy and financial leverage with stock price volatility. The theoretical implications of this study are that it is able to support the signaling theory and the "bird in the hand" theory, while its practical implications can be a benchmark for companies and investors in making decisions.